Study on adaptability of rheological index of nano-PUA-modified asphalt based on geometric parameters of parallel plate - Sun Xiaolong (De Gruyter, 2021)
To clarify the influence of geometric parameters of parallel plate on rheological properties of polyurea elastomer (PUA)-modified asphalt, nano-PUA powder was prepared, and nano-PUA powder modifier was modified by using high-speed shearing apparatus. The apparent viscosity of modified asphalt was evaluated by Brookfield viscosity. The rheological parameters of PUA-modified asphalt were determined by comparing the rheological test results of temperature scanning, frequency scanning, and multiple stress creep recover test using 8 and 25 mm parallel plates. Results indicated that the higher the content of nano-PUA modifier was, the better the high-temperature performance of asphalt would be. When using the 8 mm parallel plate, the high-temperature performance of modified asphalt was worse than that of matrix asphalt, and the PUA modifier would lead to a negative effect on the rheological property of asphalt. Regarding the 25 mm parallel plate, the high-temperature performance of modified asphalt was better than that of matrix asphalt, which was contrary to the results of 8 mm parallel plate. The rheological test results using 25 mm parallel plate were consistent with the results of Brookfield viscosity, indicating that 25 mm parallel plate was more suitable for evaluating the rheological performance of PUA-modified asphalt.